Transformation and Strategy of Islamic Banking in Realizing an Inclusive Economy in the Digital Era - Guntur Wahyudi; Ahmad Budi Susetyo (Penerbit Hellow Pustaka, 2026)
This study aims to examine the contribution of Islamic banking in driving national economic growth and to understand how Islamic principles are able to answer the challenges of digital transformation in the financial sector. Islamic banking is a financial institution that operates based on Islamic principles, such as justice, partnership, and avoidance of usury, by prioritizing a profit-sharing system through contracts such as mudharabah, musyarakah, murabahah, and ijarah. In the context of Indonesia, the existence of Islamic banks has shown significant development, supported by the largest Muslim population in the world and increasing public awareness of ethical and fair finance. Data from Bank Indonesia shows a stable growth in the number of Islamic institutions, as well as the expansion of operational networks in various regions. This study also discusses the importance of digital transformation in improving the efficiency, quality of service, and competitiveness of Islamic banking in the technological era. The results of the study show that Islamic banking not only plays a role as a business entity, but also as a strategic socio-economic instrument in creating sustainable public welfare. Thus, the Islamic financial system has great potential to become the foundation of an inclusive and equitable national economy in the future.